Kinetic studies on the tert-butylation of toluene over H-BEA zeolite. (June 2016) - Wang, Yuanyuan; Song, Hua; Song, Hualin; Sun, Xinglong; Wang, Xueqin
The highly selective synthesis of 4- tert -butyltoluene from toluene with tert -butyl alcohol over zeolite catalysts was performed in the liquid phase. The order of activity for alkylation over zeolite catalysts was as follows: H-BEA > H-Y > H-MOR > H-ZSM-5. The main reaction products observed were 4- tert -butyltoluene and 3- tert -butyltoluene. 2- tert -Butyltoluene was completely absent in the product. A kinetic study of the reaction of toluene with tert -butyl alcohol over pure H-BEA (Si/Al = 25) was performed. Experimental runs were conducted at 160, 170, 180 and 190 °C and reaction times of up to 240 min. Based on the results obtained, a simplified kinetic model was developed. The kinetics could be described by the pseudo first-order model.